The Amygdala - Where Emotions Shape Perception, Learning and Memories 2017
DOI: 10.5772/intechopen.68618
|View full text |Cite
|
Sign up to set email alerts
|

The Amygdala and Anxiety

Abstract: The amygdala has a central role in anxiety responses to stressful and arousing situations. Pharmacological and lesion studies of the basolateral, central, and medial subdivisions of the amygdala have shown that their activation induces anxiogenic effects, while their inactivation produces anxiolytic effects. Many neurotransmitters and stress mediators acting at these amygdalar nuclei can modulate the behavioral expression of anxiety. These mediators may be released from different brain regions in response to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 232 publications
(256 reference statements)
0
7
0
Order By: Relevance
“…Several brain regions have been associated to anxiety in humans and rodents, among which, the amygdala has shown to be pivotal in orchestrating behavioral responses to both fear and anxiety (Tovote et al, 2015). Other brain areas that have been associated to anxiety include the bed nucleus of the stria terminalis, hippocampus, septum, paraventricular nucleus of the hypothalamus, ventral tegmental area and locus coeruleus, among others (reviewed in Linsambarth et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several brain regions have been associated to anxiety in humans and rodents, among which, the amygdala has shown to be pivotal in orchestrating behavioral responses to both fear and anxiety (Tovote et al, 2015). Other brain areas that have been associated to anxiety include the bed nucleus of the stria terminalis, hippocampus, septum, paraventricular nucleus of the hypothalamus, ventral tegmental area and locus coeruleus, among others (reviewed in Linsambarth et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that functional and anatomical changes occur in the amygdala following acute and chronic stress. The level of general anxiety and spine density of principal neurons of the basolateral amygdala have been reported to increase 10 days after acute stress in rodents (Linsambarth et al., 2017). Chronic immobilization stress can induce more robust anxiety‐like behaviors in rodents, and within 24 h after stress cessation, anxiety is significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…THC (tetrahydrocannabinol) and nicotine both trigger dopamine release, low levels of which are related to anhedonia 21 , 22 . Dopamine has also been associated with anxiety as it is released into the brain regions associated with anxiety 23 , including the amygdala 24 . Along with serotonin, dopamine has also been found to play a physiological role in social anxiety disorders 25 .…”
Section: Introductionmentioning
confidence: 99%